Exploring the power of electronic word-of-mouth in the services industry - Kaufmann, Hans Ruediger, 1958-; Loureiro, Sandra Maria Correia, 1967- (Business Science Reference, an imprint of IGI Global, 2020)
"This book examines the importance and the effective utilization of eWOM content for the positioning of products and services that illustrate the value of user generated content for influencing customer decision making in diverse business sectors"--